Edukasi Penggunaan Antibiotik Yang Rasional Kepada Masyarakat - Fauziah, Dewi Winni; Jannah, Syauqul; Mulyani, Elly; Ers, Dina; Hariyani, Gusti; Amanda, Kurnia; Metri Erawati; Nurbayu Rizky; Ratna Yulinda; Sindi Rahayu; Yelly Dimas; Roki Pernandes (JURNAL BESEMAH, 2024)
Antibiotics are drugs or substances produced by microbes, especially fungi, which can inhibit/eradicate other microbes (microorganisms/bacteria), especially microbes that are detrimental to humans, namely microbes that cause infections in humans. Antibiotics are not effective in treating viral, fungal, or other non-bacterial infections, and each antibiotic varies greatly in its effectiveness against different types of bacteria. The use of antibiotics is certainly expected to have a positive impact, but irrational use of antibiotics will have a negative impact. One of the negative impacts of irrational use of antibiotics is bacteria that are resistant to antibiotics. In community service, the target group was approximately 20 people, almost all of whom did not know that antibiotics should not be purchased freely without a prescription from a doctor and that irrational use could increase the impact of resistance. This can be caused by a lack of public knowledge regarding the use of antibiotics and a lack of education by health workers.